Risk of Comorbidities Following Physician‐Diagnosed Knee or Hip Osteoarthritis: A Register‐Based Cohort Study. Issue 10 (22nd June 2022) - Dell'Isola, Andrea; Pihl, Kenneth; Turkiewicz, Aleksandra; Hughes, Velocity; Zhang, Weiya; Bierma‐Zeinstra, Sita; Prieto‐Alhambra, Daniel; Englund, Martin
Abstract : Objective: To estimate the risk of developing comorbidities in patients after physician‐diagnosed knee or hip osteoarthritis (OA). Methods: This was a cohort study using Swedish longitudinal health care register data; we studied residents in the Skåne region age ≥35 years on January 1, 2010 who were free from diagnosed hip or knee OA (n = 548, 681). We then identified subjects with at least 1 new diagnosis of knee or hip OA (incident OA) between 2010 and 2017 (n = 50, 942 considered exposed). Subjects without diagnosed OA were considered unexposed. From January 2010 both unexposed and exposed subjects were observed for the occurrence of 18 different predefined comorbidities until either relocation outside of the region, death, occurrence of the comorbidity, or December 2017, whichever came first. We calculated unadjusted hazard ratios (HRs) and adjusted HRs of comorbidities using Cox models with knee and hip OA as time‐varying exposures. Results: Subjects with incident knee or hip OA had 7% to 60% higher adjusted HRs (range 1.07–1.60) of depression, cardiovascular diseases, back pain, and osteoporosis than individuals without an OA diagnosis. An increased risk of diabetes mellitus was found only for knee OA (adjusted HR 1.19 [95% confidence interval 1.13–1.26]). For the rest of the diagnoses, we found either no increased risk or estimates with wide confidence intervals, excluding clear interpretations of the direction or size of effects. Conclusion: Incident physician‐diagnosed knee and hip OA is associated with an increased risk of depression, cardiovascular diseases, back pain, osteoporosis, and diabetes mellitus. However, the latter was only found for knee OA.